Experimental discussions on operating frequencies of a bidirectional isolated DC-DC converter for a battery energy storage system - Tan N.M.L.; Abe T.; Akagi H. (2023)
This paper presents a high-efficiency bidirectional isolated dc-dc converter for a battery energy storage system connected to the grid. It discusses the design of the converter, an optimal operating frequency range, and the optimal dead times for a 6-kW, full-bridge, bidirectional isolated dc-dc converter with focus on improving converter efficiency. This paper also provides a power-loss breakdown of the dc-dc converter at the rated power. The optimal frequency range of the dc-dc converter is defined by making its frequency-dependent loss equal to its frequency-independent loss. The optimal dead time is defined by one-fourth of the resonant period. The maximum efficiency of the dc-dc converter operating at 4 kHz is measured at 98.1% during battery charging and at 98.2% during battery discharging. The converter maintains a high efficiency of more than 97% in a wide range of power transfer. 2013 IEEE.